Activité amylasique chez mya arenaria l. - Roșoiu, Natalia; Stoica, Steliana (Cercetări Marine - Recherches Marines, 2026)
The paper present8 results of amylase extraction from hepatopancreas and whole soft tissue of Mya arenaria L., as well as biochemical characterization of the extract. Experimental data attest remarkable amylase activity at pH 6.9 – 7.15 and 33°C temperature.